Kampanye Penggunaan Earphone Yang Aman Bagi Kesehatan Telinga Di Kota Palembang - Shafa Naila Dyana; Aji Windu Viatra; Heri Iswandi (VisArt: Jurnal Seni Rupa dan Design, 2024)
The age of development is increasingly advanced in a sophisticated era of hearing-bound audio, the Earphone, which is a small audio device used by users by pressing or inserting it into their ear channels. This campaign was designed comprehensively, ranging from problem analysis to the development of visual strategies and concepts relevant to the people of Palembang. In-depth research highlights ear health risks due to unwise use of earphones, and this campaign aims to raise public awareness. The campaign uses visual elements such as ears and urban imagery, as well as various media such as motion graphic videos, posters, t-shirts, and leaflets to reach a wide audience. Exhibition results show the campaign is effective in changing people's behavior, raising awareness of the importance of safe use of earphones, and providing a basis for continuous education in maintaining hearing health